Advancements in the optical damage resistance of ion beam sputter deposited interference coatings for high energy lasers - Schiltz, Drew, author; Menoni, Carmen, advisor; Marconi, Mario, committee member; Bradley, Mark, committee member (Colorado State University. Libraries, 2015)
The work presented in this thesis is dedicated toward investigating, and ultimately improving the laser damage resistance of ion beam sputtered interference coatings. Not only are interference coatings a key component of the modern day laser, but they also limit energy output due to their susceptibility to laser induced damage. Thus, advancements in the fluence handling capabilities of interference coatings will enable increased energy output of high energy laser systems. Design strategies aimed at improving the laser damage resistance of Ta2O5/SiO2 high reflectors for operation at one micron wavelengths and pulse durations of several nanoseconds to a fraction of a nanosecond are presented. These modified designs are formulated to reduce effects from the standing wave electric field distribution in the coating. Design modifications from a standard quarter wave stack structure include increasing the thickness of SiO2 top layers and reducing the Ta2O5 thickness in favor of SiO2 in the top four bi-layers. The coating structures were deposited with ion beam sputtering. The modified designs exhibit improved performance when irradiated with 4 ns duration pulses, but little effect at 0.19 ns. Scaling between the results from testing at these two pulse durations shows deviation from τ1/2 scaling, where τ is the pulse duration. This suggests possible differences in the initial damage mechanism. Also presented are results for at-wavelength optical absorption losses measured with photothermal common-path interferometry and surface roughness measurements with atomic force microscopy. Further studies on the damage thresholds of interference coatings operating at 1.6 micron wavelength and 2 picosecond pulse durations are presented. High reflection and anti-reflection coating structures were fabricated with varied high index materials: HfO2, Y2O3 and Ta2O5. For damage testing, an optical parametric chirped pulse amplifier was fabricated and implemented. This source is capable of producing ~5 millijoule pulses with a tunable wavelength between 1.5 and 2 micron. When investigated at 1.6 micron wavelength, the interference coatings exhibit ultra-low absorption losses and damage thresholds at ~7.0 J/cm2 and 3.5 TW/cm2 peak intensities, near that of the infrared grade fused silica substrates they are deposited on. Furthermore, interference effects and lower band gap materials do not impair the damage threshold. This behavior is significantly different than what has previously been observed at similar pulse durations and more common laser wavelengths around 0.8 to 1 micron. I show that conventional rate equation modeling proves inadequate at describing the obtained results.
Keywords: high reflector; ion beam sputtering; optical coating; interference coating; high energy laser; laser damage